2016
DOI: 10.1007/s00404-016-4060-7
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular versus intravenous prophylactic oxytocin for postpartum hemorrhage after vaginal delivery: a randomized controlled study

Abstract: Using oxytocin by intravenous and intramuscular route has a similar efficacy and adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 15 publications
5
18
0
2
Order By: Relevance
“…Blinding of the clinicians, participants, and researchers was not mentioned and no difference was found in measured blood loss or PPH 27. The other study compared oxytocin 10 IU intravenous at 1 mL/min with oxytocin 10 IU intramuscularly 28. Birth attendants and participants were not blinded but the research team who performed the measurement of blood loss were blinded.…”
Section: Discussionmentioning
confidence: 99%
“…Blinding of the clinicians, participants, and researchers was not mentioned and no difference was found in measured blood loss or PPH 27. The other study compared oxytocin 10 IU intravenous at 1 mL/min with oxytocin 10 IU intramuscularly 28. Birth attendants and participants were not blinded but the research team who performed the measurement of blood loss were blinded.…”
Section: Discussionmentioning
confidence: 99%
“…Four trials were considered to have an unclear risk of selection bias as the methods to describe adequate random sequence generation were not reported or inadequately described [14,15,28,42]. There was an unclear risk for five trials [19,28,29,35,39] concerning allocation concealment as it was not reported appropriately. The Diop 2016 [11] and Raghavan 2015 [21] trials were cluster randomised trials meaning allocation would have been known in advance so were judged to be high risk for inadequate allocation concealment.…”
Section: Risk Of Bias Of Included Trialsmentioning
confidence: 99%
“…Detection bias showed similar results with 50% of trials deemed low risk, 17% unclear and 33% high risk. The large number of trials judged to be unclear or high risk for performance and detection bias were commonly due to difficult blinding participants and personnel to interventions due to the differences in administration [11,16,19,21,22,31,32,35,39,41,42,44], unclear reporting of methods [28,29] and a likelihood that blinding could be broken [18,20]. The Deneux-Tharaux 2013 [32] and Groot 1996 [44] trials were judged to be high risk of performance bias but low and unclear risk of detection bias, respectively, due to the use of objective measurements for the primary outcome.…”
Section: Risk Of Bias Of Included Trialsmentioning
confidence: 99%
See 2 more Smart Citations